Characteristic analysis of lightning activities on the Yungui Plateau using ground-based remote sensing - Liu, Yinping; Jiang, Yuhui; Gao, Qisen; Shi, Zheng; Jiang, Zhuyi; Hu, Jiarui (Frontiers in Environmental Science, 2022)
The spatiotemporal distribution of cloud-to-ground (CG) lightning activities on the Yungui Plateau is investigated in this study by using the 5-year dataset (2016-2020) from the ground-based National Lightning Detection Network (CNLDN). The correlations between the lightning activities and different meteorological factors in the region are also analyzed. The results show that there is an obvious difference in the spatial distribution of lightning activities on the Yungui Plateau during the five years, with high lightning density in the east and low lightning density in the west. The lightning activities shift and gather more towards the eastern plateau especially after 2019. Affected by the quasi-stationary front in Kunming, the spatial distributions of lightning flashes in cold and warm seasons are different. On the other hand, the frequency of the lightning activities varies from year to year, such as the surge in 2019. But in general, 62% of the lightning activities are produced in summer and the lightning flashes occur more often in the afternoon and evening on the Yungui Plateau. Additionally, it is found that lightning activities in the five years are closely related to precipitation and temperature, while there is a weak correlation with relative humidity and almost no correlation with sensible heat flux. The analysis also indicates that the CAPE×P (convective available potential energy times precipitation rate) proxy can be effectively used to describe and predict lightning activities on the Yungui Plateau as the lightning flashes corresponds well to CAPE×P, especially of the spatial distribution.